KUTIPAN DAN AGIHAN ZAKAT DI WILAYAH PERSEKUTUAN KUALA LUMPUR BAGI TEMPOH 1985-1995: SATU PEMERHATIAN - Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
Zakat is seen as one of the mechanism in eradicting poverty in Muslim society. However, there are some problems regarding the collection and distribution of zakat. The article focuses on the institutions involved directly with the collection of zakat i.e Baitulmal or Pusat Pungutan Zakat. It also analyses factors contributing to the rise of collection and the trend of expenditure after the privatisation of PPZ in Wi/ayah Persekutuan.